Preventing and containing trypanocide resistance in the cotton zone of West Africa - Clausen, Peter-Henning; Bauer, B.; Zessin, K.H.; Diall, O.; Bocoum, Z.; Sidibe, I.; Affognon, Hippolyte D.; Waibel, H.; Grace, Delia; Randolph, Thomas F. (Hindawi Limited, 2010)
Trypanocidal drugs are the most commonly purchased and used livestock input by resource-poor farmers in sub-Saharan Africa. The effective use of trypanocidal drugs by smallholder farmers is threatened by the development of widespread resistance. This is a particular concern for smallholder crop-livestock farmers in the cotton zone of West Africa. A recent project funded by the Germany Ministry for Economic Cooperation and Development (BMZ) confirmed significant resistance to trypanocidal drugs in villages with high trypanosomosis risk in Burkina Faso and Mali. Strategies for resistance prevention were investigated. Keeping trypanotolerant cattle was found to be an effective disease management strategy, but farmers' preference for trypano-susceptible breeds, for reasons unrelated to animal health, suggest that the intromission of zebu genotype will continue. Community vector control was found to be effective in managing trypanosomosis in the presence of resistance and the high-level participatory approach tested was found to be more sustainable than low-level approaches previously used in the region. This suggests that participatory vector control with appropriate external support is likely to be a viable option for implementing resistance 'clean-up'. Promoting rational drug use (RDU) emerged as a promising prevention strategy, with clear improvements in farmer knowledge, farmer practice and animal health outcomes. However, policy studies showed low understanding of the problem of resistance and the absence of an enabling environment for RDU. Engagement was initiated with actors involved in the problem of resistance and for its solution, including manufacturers, sellers and users of drugs, regulators and extension providers.